Potential of spherical virtual-based video reality (SVVR) through smartphone in learning Indonesian in the vocational education system - I Wayan Dian Eka Rahmanu; I Putu Yoga Laksana; Ida Bagus Artha Adnyana; I Gusti Putu Sutarma; Ni Putu Somawati; I Made Riyan Adi Nugroho (Politeknik Negeri Bali, 2022)
In the lens of technology used in classroom instruction, the 360-video virtual reality begins to use in the education field. This study aimed to identify the Indonesian language students in the higher education level perceptions of the use of SVVR (Spherical Virtual-based Video Reality) which was operated through the smartphone. The performance expectancy (PE) and effort expectancy (EE) in the UTAUT theory was employed to assess the data. There were 131 sophomores who learn the Indonesian language in the tourism department in the State Polytechnic of Bali involved to provide specific arguments through the questionnaire. The result of the study explained that learners in the Polytechnic education system were keen to engage SVVR (Spherical Virtual-Video Based Reality) during the teaching and learning process. Additionally, this learning medium elevated students’ urge significantly in learning the Indonesian language. Subsequently, the SVVR will be a promising tool employed by the lecturer who teaches the learners in the applied education system. These learning materials ought to be explored and developed more systematically by lecturers in underpinning students’ demand for knowledge and materials understanding in vocational education.